2017
DOI: 10.1186/s41935-017-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

A study of medico-legal aspects of death due to burns at a tertiary care centre in Mumbai, India

Abstract: Background: Fire is a well-known double edged sword for human beings as it served as well as destroyed mankind. Death due to thermal burns is a burning topic all over the globe. Material and method: A total of 109 cases of death due to fatal burns were brought for autopsy at a tertiary care centre in Mumbai, India during the period January 2014 to July 2015, were studied. A specially prepared proforma containing medico-legal aspects of death due to burns was filled. It was analysed by using Microsoft excel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
2
2
Order By: Relevance
“…Similar findings were found by other studies as Sharma et al, (2006), Dasari et al, (2013) and Vidhate and Pathak(2017). Also Taylor et al, (2014) found a significant association between septicemia in burn cases and occurrence of death.…”
Section: Resultssupporting
confidence: 91%
“…Similar findings were found by other studies as Sharma et al, (2006), Dasari et al, (2013) and Vidhate and Pathak(2017). Also Taylor et al, (2014) found a significant association between septicemia in burn cases and occurrence of death.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, These findings contradicted those of Vidhate & Pathak (2017), who found that the majority of deaths were suicide in origin, followed by homicidal, and finally, accidental. Different lifestyles, beliefs, and civilizations may be to blame for the large disparities.…”
Section: Discussioncontrasting
confidence: 66%
“…However, in a study by Prajapati,9 poisoning (35.51%) was the commonest cause of suicidal deaths followed by hanging (31.16%) and burns (27.54%). Interestingly, suicide by burn was also observed in our study (2.7%), however, in comparison with other studies, 10,11 it was found to be much lesser, this could be due to nonexistence of a dowry system, which is the root cause of bride burning in other parts of the country. 2 Among the cases of suicides in our study, the majority were in the age group of >10-20 years, which was similar with the study done by Ijomone et al 6 However, in a study by Nath et al, 11 maximum cases (37.96%) were seen in the age group of 21-30 years.…”
Section: Discussioncontrasting
confidence: 71%